Interference elimination based spectrum allocation algorithm for cognitive radio - Wen-feng DU; Ya-tao LIU; Zhong MING; Yin-xue SUI (Tongxin xuebao)
With the spectrum allocation process in cognitive radio network,an interference elimination based spectrum allocation algorithm was proposed to improve the utilization of spectrum by allocating available spectrum to all cognitive users which can simultaneously access the same spectrum without interference.Meanwhile,this algorithm would allocate spectrum to cognitive user,which had not been assigned in previous allocation process,with reference to the amount of available spectrums in the initial stage to optimize t fairness of spectrum allocating process.Extensive simulation results show the proposed algorithm can achieve better throughput when the amount of available spectrum is far less that of cognitive user.